Pelaksanaan Perlindungan Hukum Pekerja Anak Di Kawasan Ekonomi Khusus Mandalika - Milano, Bagus Shelva; Adha, Lalu Hadi (Fakultas Hukum Universitas Mataram, 2024)
This research aims to determine the regulations on legal protection for underage child workers and to assess the supervision provided by the Regional Technical Implementation Unit for the Protection of Women and Children in the Mandalika Special Economic Zone in relation to child workers. This writing is empirical in nature, utilizing qualitative data analysis techniques. The research findings indicate that the Indonesian government has implemented regulations and supervision measures to safeguard child workers. These include the enactment of Law No. 35 of 2014 concerning Child Protection and Ministerial Regulation on the Empowerment of Women and Child Protection of the Republic of Indonesia No. 4 of 2018, which provides guidelines for establisment of UPTD PPA. There is a need for active involvement from local governments to ensure the effective implementation of child protection measures.